A Vocational School Cutting-Edge Learning Strategy: Examining Gamification Towards Student Engagement and Achievement - Nur Rohmah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
The digital era facilitates vocational-based school learning by using innovative and digital methods. Learning media using gamification tends to be better and more relevant for students because it follows their age. This study aims to analyze the effect of gamification and student engagement on student achievement moderated by motivation. The study was conducted on vocational-based secondary school students in Central Java, involving 174 samples. The results showed that gamification and student engagement affected student achievement. Gamification affects student engagement, and motivation strengthens the effect of gamification and student engagement on student achievement. This study confirms that the gamification process in the learning process enhances the interaction between students. Research indicates that relevant gamification is implemented in vocational-based schools. Research demonstrates that motivational gamification has a critical role in increasing student achievement. Schools can adopt gamification methods to improve student learning abilities and achievement so that vocational schools acquire skilled students.